Optimization of Biocompatibility of Natural Polymer Hydrogels for Targeted Drug Delivery Applications - Lee, Ava; Tan, Jaden; Chan, Rachel (Yayasan Adra Karima Hubbi, 2024)
This study aims to optimize the biocompatibility of natural polymer hydrogels for targeted drug delivery applications. Crosslinking modifications are applied to natural polymers such as alginate, agarose, and chitosan, with the aim of increasing cell viability and reducing cytotoxicity. The results showed that modified hydrogels had higher cell viability (85–90%) and lower cytotoxicity compared to unmodified hydrogels. In addition, these modifications do not trigger immunological or inflammatory reactions in the cells of the human body tested. This study suggests that the crosslinking technique can be an effective solution in developing more biocompatible natural polymer hydrogels, which can be used for targeted drug delivery applications. However, for broader clinical applications, further research is needed to explore other modification methods and test more types of polymers.